Atypical Gaze Cueing Pattern in a Complex Environment in Individuals with ASD. - Zhao, Shuo; Uono, Shota; Yoshimura, Sayaka; Kubota, Yasutaka; Toichi, Motomi (Journal of Autism & Developmental Disorders, 2017)
Clinically, social interaction, including gaze-triggered attention, has been reported to be impaired in autism spectrum disorder (ASD), but psychological studies have generally shown intact gaze-triggered attention in ASD. These studies typically examined gaze-triggered attention under simple environmental conditions. In real life, however, the environment is complex. Previous studies have shown that an enhanced cueing effect was found when using eye gaze compared with arrow cues in unpredictably complex conditions in typically developing (TD) individuals. However, in the current study, compared with TD individuals, the cueing effect failed to enhance when using eye gaze compared with arrow cues under complex conditions in individuals with ASD. This may reflect the atypical style of gaze-triggered attention when individuals with ASD adapt to environmental complexity.